Migration of a Levonorgestrel - Releasing Intrauterine Device (Lng-Iud): Can We Trust on Ultrasound Image? - Corleta, Helena von Eye; da Silva, Ana Luiza Berwanger; Lago, Suzana Cardona; Capp, Edison (Clinical and Biomedical Research, 2010)
<span style="font-size: 10pt; line-height: 115%; font-family: ";Arial Narrow";; mso-fareast-language: EN-US; mso-ansi-language: PT-BR; mso-fareast-font-family: Calibri; mso-bidi-language: AR-SA; mso-bidi-font-family: Arial;">We report the case of a nulliparous 33-year-old woman who had a uneventful insertion of levonorgestrel-releasing intrauterine device (LNG-IUD; Mirena, Schering, Brazil) inserted on august/2005. She was amenorrheic from august 2005 to may 2006, when she referred the beginning of an intermittent spotting. On september/2006, she had a normal transvaginal ultrasound, showing a well-placed device. One year later, she informed the occurrence of regular menstrual cycles, but with menorrhagia. At that time, during the physical examination, the retrieval thread was not visible at the cervix. Another ultrasound was then performed, showing a device outside the uterine cavity, probably in the uterine serosa